Adiponectin Receptors and Pro-inflammatory Cytokines Are Modulated in Common Variable Immunodeficiency Patients: Correlation With Ig Replacement Therapy - Polito, Rita; Nigro, Ersilia; Pecoraro, Antonio; Monaco, Maria Ludovica; Perna, Franco; Sanduzzi, Alessandro; Genovese, Arturo; Spadaro, Giuseppe; Daniele, Aurora (Frontiers in Immunology, 2019)
Adiponectin exerts beneficial pleiotropic effects through three receptors, AdipoR1, AdipoR2, and T-cadherin; it also exerts immunomodulatory effects. We previously demonstrated that adiponectin levels are altered in common variable immunodeficiency disease (CVID). The purpose of the present study was to investigate further the specific involvement of adiponectin in CVID by characterizing (i) the expression profile of adiponectin receptors on peripheral blood mononuclear cells; (ii) the levels of another relevant adipokine, namely leptin; (iii) the levels of five other cytokines (IL-2, IL-6, IL-10, TNFα, and IFNγ) in 24 patients on maintenance therapy, in 18 treatment-naïve patients (before and 24 h after the first Ig infusion) and in 28 healthy controls. We found that (i) adiponectin was down-expressed in patients on maintenance therapy and in treatment-naïve patients, and that it increased in treatment-naïve patients 24 h after the first Ig infusion; (ii) leptin expression did not differ between maintenance patients and controls either before or after the first Ig infusion; (iii) AdipoR1 expression was significantly higher on B lymphocytes, monocytes and NK cells of CVID patients than in controls; (iv) the expression of AdipoR1 and AdipoR2 on B lymphocytes, monocytes and NK cells was higher after the first Ig infusion than in treatment-naïve patients; (v) T-cadherin expression did not differ between treatment- naïve CVID patients and controls, and was not affected by Ig infusion; and (vi) IL-6, IL-8, IL-10, and TNFα levels were differently expressed in CVID patients on therapy maintenance and were not affected by the first Ig replacement therapy. This is the first study to demonstrate that the expression of AdipoRs in peripheral blood mononuclear cells from CVID patients differs from that of controls, and changes after the first Ig infusion. The specificity of adiponectin involvement in CVID is supported by the absence of changes in leptin levels and in the levels of the cytokines investigated. Taken together, these results suggest that the adiponectin system plays an important and specific role in CVID. A better understanding of adiponectin as a link in the cross-talk between the immune system and adipose tissue may provide additional benefits for the management of CVID patients.